Filsafat Ilmu Manajemen Dan Penerapannya Pada Manajemen Organisasi Sekolah - Slamet Sutresno (Jurnal Ilmiah Literasi Indonesia, 2026)
School organizational management requires not only a technical and administrative approach but also a strong philosophical foundation to ensure direction, meaning, and value. The philosophy of management science provides a fundamental framework for thinking about the nature (ontology), the acquisition of knowledge (epistemology), and the utility value (axiology) in management practice. This article aims to examine the philosophy of management science and analyze its application in school management organizations. The research method used is a literature review, examining classic and contemporary books and scientific journal articles relevant to the philosophy of science, management, and educational management. The results of the study indicate that the philosophy of management science plays a crucial role in developing a rational, systematic school management paradigm oriented toward human values ​​and educational goals. The application of the philosophy of management science in school organizations is reflected in the mission statement, decision-making, human resource management, and school performance evaluation. Thus, an understanding of the philosophy of management science serves as a strategic foundation for developing an effective, ethical, and sustainable school management organization.